Structural and optical properties of silicon nanowires synthesized by Ag-assisted chemical etching. (December 2015) - Lajvardi, M.; Eshghi, H.; Ghazi, M.E.; Izadifard, M.; Goodarzi, A.
Abstract: Metal-assisted chemical etching (MACE) of silicon in an aqueous solution of hydrofluoric acid and hydrogen peroxide is established for the fabrication of large-area uniform silicon nanowire (SiNW) arrays. The effect of the silver catalyst layer thickness on the morphology of the synthesized nanostructures and nanowires is investigated. Atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM) reveal that the morphology of the fabricated silicon nanostructures remarkably depends on the catalyst layer thickness, and an optimum layer thickness is necessary for the fabrication of SiNWs. Also the effect of different etching times on the structural and optical properties of the fabricated SiNWs is investigated. FESEM showed a linear increment of the nanowire length and slight diameter changes through different etching times. The ultralow reflectance of SiNWs in the absorption region through the measurement of specular and diffuse reflectance showed that with increase in the etching time, the total reflectance remarkably decreases. A broadband visible photoluminescence (PL) emission from these wires was observed, and it could be stated that the silicon nanocrystals (SiNCs) are mostly responsible for the PL emission. The SiNC sizes were determined by an analytical model through a frequency shift in the Raman spectrum. The synthesized optically-active SiNWs could, therefore, be considered as a promising candidate for a new generation of nanoscale opto-electronic devices.